(untitled) (International Journal of Physiotherapy, 2019)
Background: The anterior cruciate ligament (ACL) tear is the most common sports injury. Surgery is often proposed, but single-leg and double-leg static postural disorders have been discovered several months after surgery. Our aims are to compare postural disorders after ligament reconstruction by hamstring tendon graft in the three months after surgery to those caused by aging. Methods: 2 groups of subjects underwent bilateral and unilateral postural tests. An analysis of the center of pressure’s displacement is carried out for each test. Results: Comparison of the two groups shows no significant difference for the injured leg on the unilateral and bilateral tests only (p-value>0,05). Conclusion: Postural alteration after an ACL reconstruction on the injured leg and bilateral posture can be compared to postural disorders caused by age.